The land of oz: a case study of rural cluster development in Wamego, Kansas - Speirs, Leland V. Jr. (Kansas State University, 2009)
During the Industrial Revolution, economist Alfred Marshall published his classic book entitled Principles of Economics, in which he suggests that the external economies of scale (positive externalities) produced by the clustering of many small innovative businesses could rival the internal economies of scale achieved by a few large vertically-integrated businesses. The distinction between these two models of industrial organization, one based on many small innovative firms and the other based on a few large conglomerated firms, is the basis of cluster development theory. This distinction has been further developed in the economic development literature through the significant contributions of Schumpeter (creative destruction), Jacobs (necessary inefficiency), and Porter (diamond model). Modern cluster development theory expands upon the work of these classic theorists. Contributions relevant to this study include Markusen’s cluster typologies, Press and Feldman’s cluster lifecycle phases, Munnich’s rural knowledge cluster framework, and Doloreux’s case study of a rural innovation system. This case study applies the lessons of cluster development theory to an emerging cluster of businesses in Wamego, Kansas that share the common Wizard of Oz theme. While this cluster is not a “traditional” cluster (it does not benefit from positive externalities relating to product or process), it does create positive marketing externalities that significantly affect the local economy. This report names the cluster (Oz Cluster), identifies the typological structure of the cluster (hub and spoke), profiles the key actors and decisions which are shaping this emerging cluster, and concludes with lessons learned from the Oz Cluster and alternative scenarios for further cluster development. The Oz Cluster model of economic development demonstrates how communities can profit from niche-based tourism. Such economic development must focus on the establishment and growth of regionally competitive businesses with strategic competitive advantages. Alternative scenarios for further cluster development include: 1) expand the Oz theme; 2) diversify the cluster; and 3) maintain current level of success.
Keywords: Cluster development; Rural cluster; Wamego Kansas; Oz Cluster; Rural economic development; Tourism; Economics, Commerce - Business (0505); Economics, General (0501); Urban and Regional Planning (0999)